POSTCOLONIAL MIMICRY AND ETHNIC HIERARCHIES IN KHALED HOSSEINI’S THE KITE RUNNER - Athaya Haura Ibrahim; Rahayu Puji Haryanti (Universitas Islam Sumatera Utara (UISU), 2026)
This study analyzed Khaled Hosseini’s The Kite Runner (2003) to expose the legacy of colonial authoritarianism and racial hierarchies that exist within ethnic tensions. Ethnic hierarchies and authoritarian power structures often have deep historical roots and are sustained in institutions in many multi-ethnic societies, making them seem natural in social life. This research examines the representation of ethnic hierarchies in the novel, the construction of the authoritarian legacy, and its reflection on Afghanistan's broader ethnic conflict. This analysis employed a qualitative method, using Homi K. Bhabha's postcolonial theory of mimicry as the analytical framework. Primary data were drawn from the novel, supported by secondary scholarly sources. Previous studies have discussed trauma, racism, and ethnic oppression in the novel; however, limited attention has been given to how colonial authoritarian ideology is reproduced through postcolonial mimicry. This study contributes to postcolonial literary criticism by demonstrating how mimicry operates not merely as cultural imitation but as a mechanism for reproducing authoritarian violence. The findings reveal how the ethnic hierarchy is reinforced through religious discrimination, physical stereotyping, and structural exclusion. Entrenched ethnic hierarchies and authoritarian legacies, reproduced through mimicry and institutionalized by Taliban governance. The conclusion reveals how the colonial legacies continuously reproduce structures of power and racial inequality, which affirms that as a literary text, The Kite Runner reflects both personal redemption and the persistence of colonial legacies in sustaining ethnic oppression. This study is limited to textual analysis and does not address broader historical complexities.